Ideología y Emancipación Femenina en el cuento “La Tigra” de José de la Cuadra - Andino Andino, Miryam Alexandra (2024)
ABSTRACT: The present research "Ideology and Female Emancipation in the Short Story La Tigra by José de la Cuadra" set out to analyze the representation of ideology and female emancipation in the short story La Tigra by the Ecuadorian writer José de la Cuadra, using Vladimir Propp's 31 narrative functions. This work demonstrates the empowerment of women in the face of a 20th-century patriarchal system. The methodology employed was qualitative in nature. Consequently, it is a descriptive study whose corpus of analysis consisted of the narrative work in question. For the analysis and interpretation of the information, the analytic-synthetic, historical-logical, and hermeneutic methods were used, as well as documentary and content analysis techniques. The research results indicate that the story of the characters in La Tigra presents a rich tapestry of relationships and conflicts within the Miranda family of the "Tres Hermanas" estate on the Ecuadorian coast in 1935, highlighting the female protagonists as powerful and feared figures following the death of their parents. These actions turn the woman into a symbol of leadership and female emancipation, challenging the patriarchal norms of the time. The work reveals not only the strength and determination of women in an oppressive environment but also the complexities and contradictions of human relationships in a specific historical context.